Effect of Nitrogen Content on Microstructures and Mechanical Properties of WB2(N) Films Deposited by Reactive Magnetron Sputtering. Issue 12 (December 2015) - Liu, Y.M.; Deng, D.Y.; Lei, H.; Pei, Z.L.; Jiang, C.L.; Sun, C.; Gong, J.
Abstract : In the present study, WB2 (N) films are fabricated on silicon and YG8 substrates at different N2 pressures by reactive magnetron sputtering. The influence of N2 partial pressure ( P N2 ) on the film microstructure and characteristics is studied systematically, including the chemical composition, crystalline structure, residual stress, surface roughness as well as the surface and the cross-section morphology. Meanwhile, nano-indentation and ball-on-disk tribometer are performed to analyze the mechanical and tribological properties of the films. The results show that the addition of nitrogen apparently leads to the change of the structure from (1 0 1) to (0 0 1) orientation then to the amorphous structure with the formation of BN phase. And the addition of nitrogen can greatly refine the grain size and microstructure of the films. Furthermore, the residual stress of the film is also found to change from tensile to compressive stress as a function of P N2, and the compressive stress increases with P N2 . The WB2 (N) films with small nitrogen content, which are deposited at P N2 of 0.004 and 0.006 Pa, exhibit better mechanical, tribological and corrosion properties than those of other films. Further increase of nitrogen content accelerates the formation of BN phase and fast decreases the film hardness. In addition, the large N2 partial pressure gives rise to the target poisoning accompanied by the increase of the target voltage and the decrease of the deposition rate.